Measuring Financial Distress of Islamic Banks Under Pandemic and Its Determinants: Random Effect Approach - Amaroh, Siti (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
This study aimed to measure the financial distress level of banks and test the influence of fundamental factors and COVID-19 on the financial conditions. Data were collected from the quarterly financial reports of Islamic banks in Indonesia for 2019.1 to 2021.1 to find out financial conditions before and during the pandemic. Testing was carried out using a panel data regression test and the random effect model was obtained as the best for this study after going through several stages of selection. The results were essential to the empirical study repertoire during the pandemic. First, the Altman Z-Score test results varied from distress, a gray area, and safe from ten Islamic banks studied. Second, after several testing stages, it was found that capital adequacy, profitability, and financing proportion positively affected financial conditions. COVID-19 did not significantly affected the financial conditions of Islamic banks. This indicated that Islamic banks in Indonesia showed short-term stability during the pandemic. However, a more extensive observation is required to assess the long-term impact.